Analysis of Gross Motor Skills in Early Childhood Through Educational Learning - Adilah, Nida; Situmorang, Merri Natalia; Ay, Elis Louisa; Situmorang, Pince Lensi Nova (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Gross motor skills are essential to develop from an early age as they support children’s coordination, health, and overall development. Proper stimulation through play and educational learning effectively enhances motor abilities and prevents developmental delays. This study aims to analyze and explain the effectiveness of educational learning in optimally developing gross motor skills in early childhood. The research used a qualitative case study method with data collection techniques including interviews, observations, and documentation, while data validity was ensured through triangulation. The results show that the “Senam Sehat Anak Indonesia” activity trains the ability to lift hands and feet, move the head flexibly, and stretch the body. Prayer (Sholat) develops hand, head, and body movements, as well as muscle strength to support body weight. Ablution (Wudhu’) strengthens the back and hands through the act of opening taps and washing the body. Activities like beading, letter sequencing, and coloring improve balance, hand endurance, and finger-wrist flexibility through coordinated movements. Conclusion: Educational learning can stimulate various forms of gross motor skills in early childhood.